2005
DOI: 10.21273/horttech.15.3.0477
|View full text |Cite
|
Sign up to set email alerts
|

Plastics: Modifying the Microclimate for the Production of Vegetable Crops

Abstract: For centuries horticulturists have attempted to modify the environment in which vegetable crops are grown. A wide variety of techniques, such as glass cloches, hotcaps, cold frames, hotbeds, and various types of glass greenhouses, have been used to extend the production season. The discovery and development of the polyethylene polymer in the late 1930s, and its subsequent introduction in the early 1950s in the form of plastic films, mulches, and drip-irrigation tubing and tape, revolutionized the comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
236
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(250 citation statements)
references
References 16 publications
12
236
0
2
Order By: Relevance
“…Results from this study are consistent with those of Miles et al (2012), who observed a 1-3.6 • C reduction in soil temperature beneath biofabrics compared to PE and bioplastic films. Biofabrics are not effective conductors of thermal energy and often are not in direct contact with the soil surface; thus, biofabrics do not provide the same soil warming benefits growers expect from dark-colored PE and bioplastic films (Lamont, 2005). However, soil warming is not always a desirable effect of mulches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study are consistent with those of Miles et al (2012), who observed a 1-3.6 • C reduction in soil temperature beneath biofabrics compared to PE and bioplastic films. Biofabrics are not effective conductors of thermal energy and often are not in direct contact with the soil surface; thus, biofabrics do not provide the same soil warming benefits growers expect from dark-colored PE and bioplastic films (Lamont, 2005). However, soil warming is not always a desirable effect of mulches.…”
Section: Discussionmentioning
confidence: 99%
“…Polyethylene (PE) mulch films are most commonly used for intensive cultivation of fruits and vegetables (Lamont, 2005) and are typically the most cost-effective option for growers (Cirujeda et al, 2012); however, the short-term economic and long-term environmental costs of PE disposal have led many growers to consider alternatives. Possible alternatives to PE include organic mulches derived from agricultural or urban byproducts and waste (e.g, straw mulch and newspaper mulch; Monks et al, 1997), paper-based mulches (e.g., WeedGuardPlus), or potentially Abbreviations: PE, polyethylene; WAT, weeks after transplanting.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, plastic mulches are films containing non-renewable fossil fuel-based plastics, particularly polyethylene. Concerns have been raised regarding the economic and environmental sustainability of polyethylene mulches, particularly related to their beginning-and endof-life [3,[5][6][7][8]. For the latter, debris and fragments formed from the weathering of polyethylene mulches [due to exposure to sunlight, especially ultraviolet (UV) radiation, and to moisture] are laborious to retrieve ($247/ha [9]), and are readily dispersed in the environment via wind and water, where they present a major hazard to animals via entanglement or ingestion, and persist for years due to poor biodegradability [2,3,10].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic agricultural mulches are important components of sustainable agriculture through serving several important roles, such as prevention of weeds, evaporative loss of soil moisture, and soil erosion [1][2][3][4]. Their employment worldwide was reported to be over 2.6 million metric tonnes in 2004, mainly used in the cultivation of fruits and vegetables [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Their employment worldwide was reported to be over 2.6 million metric tonnes in 2004, mainly used in the cultivation of fruits and vegetables [2,5]. The most common mulch feedstock, polyethylene (PE), although inexpensive, possesses several disadvantages toward sustainable agriculture, particularly relating to its beginning-and end-of-life.…”
Section: Introductionmentioning
confidence: 99%